Latin American integration effects on trade relationships: survival, growth and initial volume - Degiovanni, Pedro Gabriel; Florensa, Luis Marcelo; Recalde, María Luisa (2021)
Fil: Degiovanni, Pedro Gabriel. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas. Instituto de Economía y Finanzas; Argentina.